Intracorporeal semi‐hand‐sewn Billroth I reconstruction in total laparoscopic distal gastrectomy. Issue 3 (27th October 2020) - Kikuchi, Satoru; Kuroda, Shinji; Nishizaki, Masahiko; Kuwada, Kazuya; Takata, Nobuo; Kakiuchi, Yoshihiko; Yano, Shuya; Noma, Kazuhiro; Kagawa, Shunsuke; Fujiwara, Toshiyoshi
Abstract: Introduction: Intracorporeal Billroth I (B‐I) reconstruction using an endoscopic linear stapler (ELS) is widely performed in total laparoscopic distal gastrectomy. However, conventional procedures require many ELSs for anastomosis. Here, we introduce the novel intracorporeal semi‐hand‐sewn (SHS) B‐I reconstruction. Materials and surgical technique: After the transection of stomach and duodenum using ELS following adequate lymph node dissection, small entry holes were made on the anterior wall in the greater curvature of the stomach and the duodenal stump. The posterior walls of both the remnant stomach and the duodenum were attached with the ELS and fired to create the posterior wall of the B‐I anastomosis. All the transection line of the duodenum and one‐third of the transection line of the stomach were dissected; finally the anterior wall suturing at the anastomotic site was performed by the laparoscopic hand‐sewn technique. Discussion: SHS procedure was performed for 17 gastric cancer patients. There were no intraoperative complications or conversions to open surgery. One intra‐abdominal abscess was observed although there was no anastomotic leakage. The median reconstruction time was 48 minutes (32‐63). The SHS procedure was safe, feasible, and economical, although it requires sufficient laparoscopic suturing and ligation skill.